PENGARUH STRATEGI DIGITAL MARKETING MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI KONSUMEN PADA HONEY PET SHOP DI KABUPATEN SIDENRENG RAPPANG - Muh.Taqwa; Pratiwi Ramlan; Rahman Yakub; Haslindah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social media, particularly Instagram, is one of the most effective platforms for marketing activities as it enables businesses to reach consumers more quickly, widely, and interactively. The use of Instagram with appropriate digital marketing strategies—such as visual content, promotions, and interaction with followers—plays an important role in increasing consumers’ purchase intention.This study aims to analyze the effect of digital marketing strategies through Instagram on consumers’ purchase intention at Honey Pet Shop Rappang in Sidenreng Rappang Regency. The research method used is quantitative, with data collection techniques including online questionnaires distributed to consumers, observation of promotional activities on Instagram, and documentation studies. The data were analyzed using simple linear regression with the assistance of SPSS software.The results show that digital marketing strategies through Instagram have a positive and significant effect on consumers’ purchase intention, with a significance value of 0.001 < 0.05 and a t-value of 3.318.